Judge Stone : a novel - Davis, Viola, 1965-; Patterson, James, 1947- (Little Brown and Company, 2026)
"In Judge Mary Stone's courtroom, a person has to take a stand. In Union Springs, Alabama (population 3,314), Judge Mary Stone is a local celebrity. Born a farmer's daughter in a town where dogwoods bloom every spring and churches rise on every street corner, Judge Mary Stone holds her courtroom to the highest standard in the land. Dothe right thing, or don't do it at all. Then she draws the biggest case Alabama has ever seen. Criminally, it's open-and-shut. Ethically, there is no middle ground. Essentially, it's a choice between life and death. As she fights to determine the wisest course, Judge Stone will make history-or die trying"--